KAJIAN POTENSI DAN STRATEGI PENGEMBANGAN EKOWISATA DI CAGAR ALAM PULAU SEMPU KABUPATEN MALANG PROVINSI JAWA TIMUR - Muttaqin, Tatag; Purwanto, Ris Hadi; Rufiqo, Siti Nurul (Jurnal Gamma, 2011)
Tatag Muttaqin1, Ris Hadi Purwanto2 & Siti Nurul Rufiqo31Staf Pengajar Jurusan Kehutanan, Fakultas Pertanian dan Peternakan, Universitas Muhammadiyah Malang2 & 3 Staf Pengajar Program Pascasarjana Fakultas Kehutanan, Universitas Gadjah MadaAlamat Korespondensi : Perum GPA Blok SA 3 Ngijo Karang Ploso MalangEmail: tatag.umm@gmail.comABSTRACTSempu Island which is located in the south of the island of Java set as a nature reserve by theGovernor-General of the Dutch East Indies SK 1928. Access into this area through ecotourismBeach Blue Spring Nature Reserve, forming opinions Island Sempu a package tour with Blue SpringBeach. The research was conducted in the Island Nature Reserve Sempu Malang East Java Provincein April 2011 to March 2012. The purpose of this study was to assess the condition Sempu IslandNature Reserve, assessing tourism potential and assess appropriate strategies for the developmentof ecotourism in the area Sempu Island Nature Reserve. The study was conducted by surveymethods, data collection methods include primary and secondary data. Analysis of data to determinethe strategy of the development of ecotourism in the area of Island Nature Reserve Sempu usedSWOT analysis and to determine the best decision in the selection criteria with respect to aspects(economic, environmental and social) to approach analytical hierarchy process (AHP), is to assessthe benefits of "impact positive "and cost" negative impact "tourism development based on stakeholderperceptions.The results based on conditions on the ground shows that Sempu Island Nature Reserve hasbecome a tourist spot with tourists ± 200-300 wiatawan each week and more than doubled eachholiday season with a growth rate of 4.97% of tourists visit each year, an estimated tourists in theyear 2021 reach ± 17 715 tourists. The results of SWOT analysis and AHP referrals generatedtourism development strategy are: to evaluate the function and status of the area, building a commonperception and concept development of ecotourism among stakeholders, development of eco-tourismin the two regions are Sempu Island Nature Reserve as a provider of travel products and naturalattractions such as Blue Spring Beach as a provider of tourist facilities and accessibility, communityempowerment in managing Sempu Island Nature Reserve in the planning, implementation and evaluationin the development of eco-tourism, improving education and improving the quality of products andHRKeywords: Sempu Island Nature Reserve, Ecotourism, Development, SWOT, AHP